A National Engagement Model for Developing Computer Science Education in Wales - Tom Crick (Proceedings of 9th International Conference on Informatics in Schools, 2016)
Computer science education in the United Kingdom has undergone substantial scrutiny, and in England a new computing curriculum has just been introduced. However, in Wales – a devolved nation within the UK – political, geographical and socio-technical issues have hindered any substantive educational policy or curriculum reform for computer science over the past ten years. In this paper we present the activities of Technocamps, a university-based schools outreach pro- gramme founded in 2003 and its wider impact on computer science edu- cation and teachers in Wales. Furthermore, with imminent curriculum reform, we frame the wider opportunity for sustainably embedding both high-value digital competencies and computer science education – as well as changing the wider public perception and importance of computer science – as a prospective replicable case study of a national engagement model for countries with similar aspirations of becoming digitally confident and capable nations.